2017
DOI: 10.1186/s13717-017-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological fitness of brown planthopper, Nilaparvata lugens (Stål), to rice nutrient management

Abstract: Introduction: The brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), is a notorious insect pest of rice. Nutrient supplementation can alter plant biochemical compositions which may indirectly affect on ecological fitness parameters of its insect pest. However, few findings are available on nutrient-induced ecological fitness of BPH and relationship of BPH fitness parameters with its host rice plant biochemical contents. Methods: We studied the main and interaction effects of nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…However, some workers found that higher level of K was associated with a lower population of BPH possibly due to the reduced level of RS and TFA in K rich rice cultivars (Vanitha et al 2011). Correlation and PCA strongly boosted these obtained results and the possible mechanisms were also supported by Rashid et al (2017b) and Yin et al (2005). The phenolic compounds were found to be the feeding deterrents to BPH in rice and generally have a positive correlation with host plant resistance (Singh 2004).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, some workers found that higher level of K was associated with a lower population of BPH possibly due to the reduced level of RS and TFA in K rich rice cultivars (Vanitha et al 2011). Correlation and PCA strongly boosted these obtained results and the possible mechanisms were also supported by Rashid et al (2017b) and Yin et al (2005). The phenolic compounds were found to be the feeding deterrents to BPH in rice and generally have a positive correlation with host plant resistance (Singh 2004).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, Rashid et al (2017b) linked higher K level with a lower level of TFA in the rice plants and observed the increment of both the compounds after BPH feeding.…”
Section: Discussionmentioning
confidence: 91%
“…These differences in resistance levels in geographically different populations may reflect natural variation between populations. According to Rashid et al (2017), population abundance and insect pest dynamics is dependent on ecological fitness parameters, such as survival rate. Based on the slope value, the one with the lowest slope was at the Mungkid location.…”
Section: Determination Of Lc50 N Lugens Field Population Against Pymetrozine Insecticidementioning
confidence: 99%
“…Currently, the insect pest has been described as the most damaging rice pest in Asia [ 5 , 6 , 7 , 8 ]. Heavy infestation by BPH can result to direct and indirect yield losses of 20–80% in sensitive cultivars [ 9 , 10 , 11 , 12 , 13 ]. When the pest damage becomes established, it is very difficult to control and, thus, yield reduction is certain [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that favour BPH development include the adoption of high-yielding BPH-sensitive varieties to replace traditional resistant ones in recent years [ 15 ], higher humidity (greater than 80%), temperature of about 25 to 32 °C, and application of nitrogenous fertiliser beyond the recommended rate [ 16 ]. Others are higher plant density, continuous submergence of the host in the field and indiscriminate application of pesticide at the early development of the host, which destroys their natural enemies [ 12 , 16 , 17 ]. Attack by BPH causes a reduction in photosynthetic rate, leaf area, chlorophyll content, nitrogen level of leaf and stem and dry matter accumulation in rice varieties that are susceptible [ 18 ].…”
Section: Introductionmentioning
confidence: 99%